Histological study in the digestive tract on larval development of rainbow trout (Oncorhynchus mykiss, Walbaum, 1792) - Sarieyyüpo?lu, Mustafa; Girgin, Aydm; Köprücü, Sibel (My University, 2000)
In this study the development of the digestive tract of newly hatched rainbow trout (Oncorhynchus mykiss) larvae were examined. The digestive tract was attached to the anus a few hours after hatching. On the second day their mouths were open and the differentiation in the esophagus started. Mucosal folds contained a large quantity of cubic epithelium and goblet cells. Goblet cells were stained positively with Alcian blue and also stained negatively with P.A.S. The wall of the esophagus consisted of a circular muscle layer and a thin tunica serosa. It was possible to see a thin longitudinal muscle layer in the inner side, on the tenth day. Two days after hatching, the stomach was formed as a continuing part of the esophagus mucosa. Goblet cells were not observed. The wall of the stomach consisted of a circular muscle layer and a thin tunica serosa. The first signs of the stomach glands were observed on the 22nd day. In the intestine the basophilic granular cytoplasm of epithelial cells was stained lightly with P.A.S. on the second day after hatching. The first goblet cells were seen on the third day. The liver sinusoids were observed in the first 3-4 days. The cells were stained positively with P.A.S. because of the glycogen concentration.
Keywords: Development; Histology; Rainbow trout (Oncorhynchus mykiss)